A law which favours forgers: Land fraud in two torrens jurisdictions - TANG, Hang Wu (Institutional Knowledge at Singapore Management University, 2011)
Discussion about land fraud in Singapore and Malaysia with emphasis on concepts of immediate indefeasibility and deferred indefeasibility.Argument that variour aspects of conveyancing such as attestation of documents, procedures for obtaining replacement certificate of title and process of identification play crucial roles in fraud protection.